2014
DOI: 10.1093/infdis/jiu439
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Monocytes Contribute to Pathologic Immune Response inLeishmania braziliensisInfections

Abstract: Ulcer development in patients with cutaneous leishmaniasis (CL) caused by Leishmania braziliensis is associated with high levels of tumor necrosis factor (TNF). We found that early after infection, before ulcer development, the frequency of CD16(+) (both intermediate [CD14(+)CD16(+)] and nonclassical [CD14(dim)CD16(+)]) monocytes was increased in the peripheral blood of patients with L. braziliensis, compared with uninfected controls. These results suggest that CD16(+) monocytes might promote disease. Also, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 48 publications
(58 reference statements)
4
77
0
Order By: Relevance
“…The importance of CD14 + CD16 + monocytes in inflammation and tissue injury is also well documented in reports of laboratory and clinical studies 12 18 33 34. These cells are considered as inflammatory monocytes, because they express a higher level of HLA-DR, have higher ability of phagocytosis, produce more proinflammatory cytokines and chemokines such as TNF-α, interleukin 6, interferon γ, macrophage inflammatory protein 1α and 1β,19 34 35 and most importantly, are expanded in many inflammatory disorders. Mouse blood and splenic Ly6c low monocytes, the counterpart of human CD14 + CD16 + monocytes, express higher TNF-α than Ly6c high monocytes 30…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The importance of CD14 + CD16 + monocytes in inflammation and tissue injury is also well documented in reports of laboratory and clinical studies 12 18 33 34. These cells are considered as inflammatory monocytes, because they express a higher level of HLA-DR, have higher ability of phagocytosis, produce more proinflammatory cytokines and chemokines such as TNF-α, interleukin 6, interferon γ, macrophage inflammatory protein 1α and 1β,19 34 35 and most importantly, are expanded in many inflammatory disorders. Mouse blood and splenic Ly6c low monocytes, the counterpart of human CD14 + CD16 + monocytes, express higher TNF-α than Ly6c high monocytes 30…”
Section: Discussionmentioning
confidence: 93%
“…Early studies demonstrated that human circulating monocytes are phenotypically and functionally heterogeneous, and can be subdivided into CD14 high CD16 − classic inflammatory monocytes and CD14 + CD16 + resident subsets 12 14–17. Other studies reported that among CD14 + CD16 + monocytes, a subset with a CD14 high CD16 + phenotype (termed as intermediate monocytes) was more closely correlated with the pathogenesis of many inflammatory diseases, exhibited a high capacity for production of tumour necrosis factor (TNF)-α, and regulated immune responses 18 19. CD14 low CD16 + monocytes (named non-classical monocytes) are smaller and less granular, and express higher levels of the C-X-C chemokine receptor (CX3CR1),15 patrol the vascular endothelium, and are involved in the innate surveillance of local tissues 15 20…”
Section: Introductionmentioning
confidence: 99%
“…Monocytes and macrophages are heterogeneous subpopulations, with killing, inflammatory, and regulatory profiles 34. Previous studies have shown a high frequency of monocytes with inflammatory profile in E-CL,14 and there is a direct correlation between the frequency of monocytes expressing toll-like receptor9 with ulcer size in CL 37. Moreover, no production rather than protection is associated with pathology in L. braziliensis infection 38.…”
Section: Discussionmentioning
confidence: 99%
“…Although an intense lymphocyte proliferation and production of IFN-γ and tumor necrosis factor is induced on Leishmania antigen stimulation of peripheral blood mononuclear cells from patients with L-CL,12 in the preulcerative phase of the disease, lymphocyte proliferation, and cytokine production is lower than in patients with L-CL 13. Nevertheless, when compared with healthy subjects, E-CL patients exhibit an increase in the frequency of inflammatory or intermediate monocytes, produce higher levels of proinflammatory cytokines, and exhibit substantial transcriptional changes at the infection site 2,14. However, the histopathological features of E-CL have not been described.…”
Section: Introductionmentioning
confidence: 99%
“…12 Products secreted by monocytes during CL include TNF, chemokines (CXCL9, CXCL10, and CCL2), and metalloproteinase-9 (MMP-9), and some reports indicate the participation of TNF and monocyte-derived MMP-9 in tissue damage during leishmaniasis. 2,13,14 Herein, we evaluated the immune response from a patient with HIV and L. braziliensis coinfection and found mononuclear phagocytes infiltrating the lesion and production of TNF, CCL2, and MMP-9 at lesion site.…”
Section: Introductionmentioning
confidence: 99%